Genocide in California - Wills, Matthew (JSTOR Daily, 2023)
The extermination campaigns against the Yuki people, sparked by the California Gold Rush and statehood, weren’t termed genocide until the mid 1970s.
United States of America
Keywords: 2023-10 October